Determining c‐Myb Protein Levels Can Isolate Functional Hematopoietic Stem Cell Subtypes. (February 2015) - Sakamoto, Hiroshi; Takeda, Naoki; Arai, Fumio; Hosokawa, Kentaro; Garcia, Paloma; Suda, Toshio; Frampton, Jon; Ogawa, Minetaro
Abstract The transcription factor c‐Myb was originally identified as a transforming oncoprotein encoded by two avian leukemia viruses. Subsequently, through the generation of mouse models that affect its expression, c‐Myb has been shown to be a key regulator of hematopoiesis, including having critical roles in hematopoietic stem cells (HSCs). The precise function of c‐Myb in HSCs although remains unclear. We have generated a novel c‐myb allele in mice that allows direct observation of c‐Myb protein levels in single cells. Using this reporter line we demonstrate that subtypes of HSCs can be isolated based upon their respective c‐Myb protein expression levels. HSCs expressing low levels of c‐Myb protein (c‐MyblowHSC) appear to represent the most immature, dormant HSCs and they are a predominant component of HSCs that retain bromodeoxyuridine labeling. Hematopoietic stress, induced by 5‐fluorouracil ablation, revealed that in this circumstance c‐Myb‐expressing cells become critical for multilineage repopulation. The discrimination of HSC subpopulations based on c‐Myb protein levels is not reflected in the levels of c‐myb mRNA, there being no more than a 1.3‐fold difference comparing c‐Myblow and c‐MybhighHSCs. This illustrates how essential it is to include protein studies when aiming to understand the regulatory networks that control stem cell behavior. Stem Cells2015;33:479–490